2001
DOI: 10.1080/01612840119739
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Aberrant Medical Humor by Psychiatric Unit Staff

Abstract: The purpose of this study was to develop a grounded theory about the joking behaviors of psychiatric unit staff. Fifty nine staff members (Male = 23, Female = 36), ages 28-62, who worked in an urban, public facility were observed in unit meetings over a two year period. Data were analyzed using the constant comparative method. Participants used aberrant humor to deal with the basic social process of facing a series of ultimately unresolvable problems. The factors involved included the organizational context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 28 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Or is it the case that certain types of humour may be less adaptive than others? Sayre (2001) studied the disparaging humour use of psychiatric nurses in relation to patients and concluded that it may have a negative impact on the therapeutic process.…”
Section: Resultsmentioning
confidence: 99%
“…Or is it the case that certain types of humour may be less adaptive than others? Sayre (2001) studied the disparaging humour use of psychiatric nurses in relation to patients and concluded that it may have a negative impact on the therapeutic process.…”
Section: Resultsmentioning
confidence: 99%
“…Assumptions about what constitutes professionalism sometimes suggest that humour is not consistent with professional conduct (Sayre 2001, Sobel 2006). Our research refutes this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence of the significance of humour in healthcare relationships. Research has addressed the social functions of humour in various settings (Rosenberg 1991, Yoels & Clair 1995, Astedt‐Kurki & Isola 2001) and the use of humour in specific settings such as psychiatry (Griffiths 1998, Sayre 2001), ICU (Thornton & White 1999) and medical education (Smith & Kleinman 1989). Despite variability in settings and approaches, findings consistently identify the importance of humour as a means of enabling communication, fostering relationships, easing tension and managing emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Since his source of data mainly involves speeches and biographies of statesmen, it is highly unlikely that he should find evidence of upward directed humour there. The idea of humour's potential for reinforcing social hierarchies appears now and then (Palmer 1994;Martin 2007), with a reference to two studies in two psychiatric wards where the high ranked staff initiated joking more often than lower ranked staff during staff meetings (Coser 1960;Sayre 2001). However, the data for these studies are from formal meetings, not recordings of what happens when the high ranked staff is not present.…”
Section: Introductionmentioning
confidence: 92%